I worked out my solution and was hoping for some input from the experts as to whether I did this correctly or not.
Thanks in advance!!
Compute the indicated derivative.
f'''(t) for f(t) = 4t2 - 12 + (4/t2)
F’(t) = (d/dt) (4t2 -12 + (4/t2)
= 8t + 4t-2
F’’(t) = (d/dt) (8t + 4t-2)
= 8 – 8t-1
F’’’(t) = (d/dt) (8 – 8t-1)
Okay, so lets see if I understand this now...., lets use the following:
Find the derivative:
f(x) = (x^3/2 - 4x) (x^4 - 3/x^2 +2)
then I would rewrite as........
= (x^3/2 -4x) (x^4 - 3x^-2 + 2)
then, take the derivative.......
f ' (x) = [((3/2 x^-3/2) - 4)(x^4 - 3x^-2 +2)] + [(x^3/2 - 4x) (4x^2 + 3x^-3)]
Ive got a headache now, btw
the derivative of x^4 is 4x^(4- 1)= 4x^3, not 4x^2, and the derivative of 3x^(-2) is 3(-2)x^(-2-1)= -6x^(-3), not 3x^(-3).
Don't worry, you'll get used to it!Ive got a headache now, btw